1999
DOI: 10.1002/(sici)1097-4695(19991105)41:2<165::aid-neu1>3.3.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Crustacean frequenins: Molecular cloning and differential localization at neuromuscular junctions

Abstract: Crustacean muscles are innervated by phasic and tonic motor neurons that display differential physiology and have morphologically distinct synaptic terminals. Phasic motor neurons release much more transmitter per impulse and have filiform terminals, whereas tonic motor neurons release less transmitter and have larger terminals with prominent varicosities. Using an antibody raised against Drosophila frequenin (frq), a calcium-binding protein that enhances transmitter release in Drosophila synaptic terminals, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…We performed a Western blot analysis on sartorius and CP muscles, with quantal content of CP NMJs being 3-4 times greater than that of the sartorius (Grinnell & Herrera, 1980), to compare their level of frequenin expression. Consistent with the data obtained from crayfish terminals (Jeromin et al 1999), we found a greater amount of frequenin protein in CP muscles (Fig. 7A).…”
Section: Effect Of Stimulation On Frequenin Expressionsupporting
confidence: 92%
See 3 more Smart Citations
“…We performed a Western blot analysis on sartorius and CP muscles, with quantal content of CP NMJs being 3-4 times greater than that of the sartorius (Grinnell & Herrera, 1980), to compare their level of frequenin expression. Consistent with the data obtained from crayfish terminals (Jeromin et al 1999), we found a greater amount of frequenin protein in CP muscles (Fig. 7A).…”
Section: Effect Of Stimulation On Frequenin Expressionsupporting
confidence: 92%
“…For example, frequenin, a well-conserved Ca 2+ -binding protein is known to enhance transmitter release in Drosophila and Xenopus nerve terminals (Pongs et al 1993;Olafsson et al 1995). Frequenin is also likely to play a role in synaptic transmission of the crayfish, since it is more prominently expressed in phasic nerve terminals compared to tonic (Jeromin et al 1999).…”
Section: Effect Of Stimulation On Frequenin Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…The KChIPs 2 and 3(b) have a variable N-terminal extension (yellow), while the other members of the family have an Nterminal myristoylation consensus sequence (a). Gly 42 and Gly 96 , which are conserved in all members of the family, are the sites of rotation following Ca 2 + binding in recoverin.…”
Section: Figure 4 Schematic Diagram Of the Domain Organization Of Thementioning
confidence: 99%